The effects of glucose-fructose co-ingestion on repeated performance during a day of intensified rugby union training in professional academy players - Hengist, A.; Watkins, J. D.; Smith, H. A.; Edinburgh, R. M.; Betts, J. A.; Roe, G. A. B.; Gonzalez, J. (Journal of Sports Sciences, 2021)
This study assessed the effects of glucose-fructose co-ingestion during recovery from high-intensity rugby training on subsequent performance. Nine professional, senior academy Rugby Union players performed two trials in a double-blind, randomized, crossover design. Identical rugby training sessions were separated by a 3-hour recovery period, during which participants ingested protein (0.3 gxkg BM/h) and carbohydrate-containing (0.8 gxkg BM/h) recovery drinks, comprised of glucose polymers (GLUCOSE ONLY) or a glucose-fructose mixture (GLUCOSE+FRUCTOSE). Performance outcomes were determined from global positioning systems combined with accelerometry and heart rate monitoring. Mean speed during sessions 1 (am) and 2 (pm) of GLUCOSE ONLY was (mean±SD) 118±6 and 117±4 m/min, respectively. During GLUCOSE+FRUCTOSE, mean speed during session 1 and 2 was 117±4 and 116±5 m/min, respectively (time x trial interaction, p = 0.61). Blood lactate concentrations were higher throughout recovery in GLUCOSE+FRUCTOSE (mean ±SD: 1-h 3.2 ±2.0 mmol/L; 3-h 2.1 ±1.2 mmol/L) compared to GLUCOSE ONLY (1-h 2.0 ±1.0 mmol/L; 3-h 1.4 ±1.0 mmol/L; trial effect p = 0.05). Gastrointestinal discomfort low in both conditions. These data suggest glucose-fructose mixtures consumed as protein-carbohydrate recovery drinks following rugby training do not enhance subsequent performance compared to glucose-based recovery drinks.